2020
DOI: 10.3803/enm.2020.35.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism Affects the Long-Term Outcomes of Patients Who Undergo Coronary Artery Bypass Grafting Surgery but Not Heart Valve Surgery

Abstract: Background The aim of this study was to determine the associations between subclinical hypothyroidism (SCH) and long-term cardiovascular outcomes after coronary artery bypass grafting (CABG) or heart valve surgery (HVS). Methods We retrospectively reviewed and compared all-cause mortality, cardiovascular mortality, and cardiovascular events in 461 patients who underwent CABG and 104 patients who underwent HVS. Results During a mean±standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Previous studies have reported increased mortality, Af, and stroke rates [5][6][7], and repeat target-vessel PCI [6] in patients with hypothyroidism who underwent CABG, and their findings were different from our results. These studies are single-center retrospective reviews that confirmed the diagnosis by routine screening of the serum levels of TSH, T3, and T4 and clinical symptoms described in medical records.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported increased mortality, Af, and stroke rates [5][6][7], and repeat target-vessel PCI [6] in patients with hypothyroidism who underwent CABG, and their findings were different from our results. These studies are single-center retrospective reviews that confirmed the diagnosis by routine screening of the serum levels of TSH, T3, and T4 and clinical symptoms described in medical records.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with advanced coronary artery disease (CAD) require a coronary artery bypass grafting (CABG). Some single-center retrospective clinical studies on the long-term prognosis of patients with hypothyroidism who underwent CABG have revealed a higher risk of revascularization, atrial fibrillation, and all-cause mortality [5][6][7] and increased risk of renal replacement therapy [4]. The exact physiology of thyroid disease and the relationship with post-CABG prognosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity between studies was moderate to substantial in the meta-analysis for subclinical hypothyroidism (42,121,123,126,130,131,136,(140)(141)(142)(143). Random effects models reveal an association to inclusive MACE, but not to study-specific MACE (Figures 8A,B).…”
Section: Outcome Main Resultsmentioning
confidence: 99%
“…In subjects with heart failure elevated TSH concentration was associated with increased hazard ratio for a composite end point ( 131 ). Patients undergoing cardiac surgery with ischaemic heart disease demonstrated elevated TSH concentration to be associated with higher all-cause and cardiovascular mortality ( 136 ).…”
Section: Clinical Evidencementioning
confidence: 99%
“…Several studies found correlations between sHypo and cardiovascular disease [ 75 , 76 ], including a comprehensive meta-analysis that demonstrated an association between cardiovascular disease risk and sHypo [ 77 ]. Long-term cardiovascular outcomes after coronary bypass grafting in patients with sHypo showed a poor prognosis [ 78 ]. However, data from a consortium of cohort studies with data from more than 75,000 participants (Thyroid Studies Collaboration) revealed no correlation with the risk of atrial fibrillation [ 79 ], heart failure [ 80 ], stroke [ 81 ], coronary heart disease [ 82 ], mortality [ 83 ], and sHypo.…”
Section: Organ-specific Considerations In the Management Of Shypomentioning
confidence: 99%